The Effect of Product Quality and Brand Image on Customer Loyalty Through Customer Satisfaction Yotta Palopo City - Gusti Ayu Widyasti (Scientia Integritas Utama, 2022)
This study aims to determine the effect of product quality and brand image on consumer loyalty through Yotta Palopo customer satisfaction. This research is a quantitative research, the data used is primary data, namely data obtained from distributing questionnaires to research objects. The population in this study are consumers who have purchased products at Yotta Palopo City. The sampling technique used purposive sampling with a total sample of 100 respondents. The analytical method used in this study is regression analysis via SPSS version 2.3. The results of the study show that (1) product quality has a positive and significant effect on consumer satisfaction Yotta Palopo City; (2) brand image has a positive and significant effect on consumer satisfaction Yotta Palopo City; (3) product quality has no significant effect on customer loyalty Yotta Palopo City; (4) brand image has a positive and significant effect on customer loyalty Yotta Palopo City; (5) customer satisfaction has a positive and significant effect on customer loyalty Yotta Palopo City; (6) product quality has a positive and significant effect on customer loyalty through Yotta Palopo City customer satisfaction; and (7) brand image has a positive and significant effect on customer loyalty through Yotta Palopo City customer satisfaction (5) customer satisfaction has a positive and significant effect on customer loyalty Yotta Palopo City; (6) product quality has a positive and significant effect on customer loyalty through Yotta Palopo City customer satisfaction; and (7) brand image has a positive and significant effect on customer loyalty through Yotta Palopo City customer satisfaction (5) customer satisfaction has a positive and significant effect on customer loyalty Yotta Palopo City; (6) product quality has a positive and significant effect on customer loyalty through Yotta Palopo City customer satisfaction; and (7) brand image has a positive and significant effect on customer loyalty through Yotta Palopo City customer satisfaction